2009
DOI: 10.1179/174328107x174618
|View full text |Cite
|
Sign up to set email alerts
|

Water modelling of level fluctuation in thin slab continuous casting mould

Abstract: A water modelling experiment was conducted to study the meniscus instability in a continuous thin slab casting mould using particle image visualisation. The results show that the level fluctuation, circulation centre position and jet impinging depth are unsteady and periodic with a similar period. The probability distributions of the fluctuating meniscus and wave height have been obtained with the highest frequency near the average position. The flow pattern and meniscus profile may be momentarily asymmetrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…However, several researchers from both industry and academia have proven various devices and operating strategies in order to improve the quality of steel produced through this process [1][2][3][4]. Surface defects and slag entrapment are significant defects that deteriorate the quality of steel that is produced by the continuous casting process [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, several researchers from both industry and academia have proven various devices and operating strategies in order to improve the quality of steel produced through this process [1][2][3][4]. Surface defects and slag entrapment are significant defects that deteriorate the quality of steel that is produced by the continuous casting process [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [2][3] studied the free surface instability in a full scale continuous thin slab casting mould using particle image velocimetry and found that the level fluctuation, the circulation center position and the jet impinging depth are unsteady with a similar period. They also found that the wave height mainly depends on the jet impinging depth and the circular center position [2][3].…”
Section: Introductionmentioning
confidence: 98%
“…The fluid flow inside the mold produces significant variations of the liquid steel free surface and therefore, is very difficult to obtain an accurate value of the level. Many experimental works have been devoted to study these variations [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Lo anterior, origina la presencia de otros fenómenos tales como vórticidades debido al flujo altamente turbulento existente al interior del molde [5][6][7]13]. Estos fenóme-nos tienen un efecto negativo ocasionando que la capa de polvos lubricantes y transferencia de calor no sean homogéneos, exista atrapamiento de escoria hacia el seno de metal líquido y agrietamientos en la superficie del planchón producido [9][10][11][12].…”
Section: Introductionunclassified